Additive value of pre-operative and one-month post-operative lymphocyte count for death-risk stratification in patients with resectable pancreatic cancer: a multicentric study. Issue 1 (December 2016) - d'Engremont, Christelle; Vernerey, Dewi; Pointet, Anne-Laure; Simone, Gaël; Fein, Francine; Heyd, Bruno; Koch, Stéphane; Vuitton, Lucine; Kim, Stefano; Jary, Marine; Lamfichek, Najib; Turco, Celia; et al.
Abstract Background Pancreatic adenocarcinoma (PDAC) incidence is increasing worldwide. Several studies have shown that lymphopenia was correlated with a poor prognosis but the potential interest to measure lymphopenia in the pre and post-operative setting as well as its added value among conventional prognostic factors was never investigated. Methods Data from two independent cohorts in whom patients underwent resection for pancreatic carcinoma were retrospectively recorded. We examined the association between perioperative findings, pre and post-operative lymphocyte counts and overall survival (OS) in univariate and multivariate analyses. Performance assessment and internal validation of the final model were evaluated with Harrell's C-index, calibration plot and bootstrap sample procedures. Results Three hundred ninety patients were included in the analysis between 2000 and 2011. Pre and post-operative lymphocyte counts were independent prognostic factors associated with OS in multivariate analysis (p = 0.0128 andp = 0.0764, respectively). The addition of lymphocyte count variable to the conventional parameters identified in multivariate analysis (metastatic lymph node ratio, veinous emboli and adjuvant chemotherapy) significantly improved the model discrimination capacity (bootstrap mean difference = 0.04; 95 % CI, 0.01–0.06). The use of a threshold and combining the categorical (≥1000; <1000) information in pre and post lymphocyte counts permitted the identification of 4 subgroups of patients with different prognosis (p < 0.0001). Finally, the description of patients in long-term remission showed that only 3 of 65 (4.6 %) patients with post-operative lymphocyte count under 1000/mm3 were alive 4 years after surgery contrary to 54 of 236 (22.8 %) patients with a post-operative lymphocyte count above 1000/mm3 . Conclusion Pre and post-operative lymphopenia are independent prognostic factors for OS and they have an additive value regarding conventional prognostic factors for death-risk stratification and to predict long-term survival. Lymphopenia should be included as stratification factors in future clinical trial assessing overall survival in pancreatic cancer patients.